The green children of Woolpit chronicles, fairies and facts in medieval England - Clark, John 1958- (Exeter new approaches to legend, folklore and popular belief, 2024)
This book introduces the story of the 'Green Children' and how it has been interpreted, retold, and reworked. Analysing the two accounts, and offering fresh translations from the Latin originals, it considers what the historians tell us happened, and then the children's own story of their homeland